2023
DOI: 10.30867/action.v8i1.616
|View full text |Cite
|
Sign up to set email alerts
|

Analisis faktor ibu terhadap kejadian stunting pada balita usia 24-59 bulan di perkotaan

Abstract: The prevalence of stunting is still high in urban areas. Maternal factors such as height, education, occupation, antenatal visits, and nutritional status have increased stunting in urban areas. The study aims to analyze the maternal factors that influence the incidence of stunting among children aged 24-59 months in urban areas. The case-control design study was conducted in May-July 2019 in Pasuruan City. Samples of 67 cases (HAZ < -2SD) and 67 controls (HAZ > -2SD) were selected by simple random sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
0
0
1
Order By: Relevance
“…Children who come from households that do not have qualified latrines or unqualified drinking water sources increase the risk of stunting. Social and community issues such as access to health services, living in rural, social, and cultural areas, agricultural systems, water, and sanitation also contribute to stunting in Indonesia (Batiro et al, 2017;Beal et al, 2018;Manggala et al, 2018;Nshimyiryo et al, 2019;Sugianti et al, 2023;Titaley et al, 2019). Other studies have also found a short relationship between parents (father and mother) and the incidence of stunting in toddlers (Miko & Al-Rahmad, 2017;Javid & Pu, 2020;Wu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Children who come from households that do not have qualified latrines or unqualified drinking water sources increase the risk of stunting. Social and community issues such as access to health services, living in rural, social, and cultural areas, agricultural systems, water, and sanitation also contribute to stunting in Indonesia (Batiro et al, 2017;Beal et al, 2018;Manggala et al, 2018;Nshimyiryo et al, 2019;Sugianti et al, 2023;Titaley et al, 2019). Other studies have also found a short relationship between parents (father and mother) and the incidence of stunting in toddlers (Miko & Al-Rahmad, 2017;Javid & Pu, 2020;Wu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…13 Namun, studi lain meloporkan bahwa di antara anak-anak di bawah usia lima tahun, tidak ada korelasi antara stunting dan jenis kelamin, urutan kelahiran, berat badan lahir, usia ibu saat hamil, tinggi badan ibu, pendidikan ibu, pekerjaan ibu, kehadiran di kelas antenatal, atau kunjungan ke layanan prenatal. 14 Kurangnya kecukupan protein, riwayat berat badan lahir rendah (BBLR), riwayat ASI tidak eksklusif, pendidikan dan pekerjaan ibu tidak memiliki korelasi terhadap kejadian stunting. 15 Dari berbagai studi terdahulu, terlihat bahwa faktor risiko kejadian stunting pada balita masih belum konsisten, sehingga perlu dilakukan penelitian terkait stunting untuk mengidentifikasi determinan kejadian stunting berdasarkan fenomena yang terjadi dilokasi penelitian.…”
unclassified